El treebank del español "IPROCOLDI": componente anotado del corpus CODIMEP-CR - Jara Murillo, Carla Victoria (2014)
This paper describes the process followed in order to create a Spanish treebank in the framework of the research project No. 745-B1-244 Interfaz para el procesamiento de corpus lingüísticos digitales – IPROCOLDI (Interface for the processing of digital language corpora). The data for the treebank was extracted from the Corpus de Mensajes Presidenciales Costarricenses (CODIMEP- CR). The interface and the treebank are located at http://163.178.116.145/iprocoldi/.